Monetary Policy in a Linearized DSGE Model (Journal of Finance, Business and Management Studies, 2021)
The study is to estimate the endogenous variables of monetary policy to understand the response and interaction among the variables. I use the linearized DSGE model, and the findings suggest that the monetary policy shock leads inflation falls and interest rate rises but change in interest rate decreases output.
Keywords: DSGE model; Forecasting; Economic policy and real GDP